Akibat Hukum Pandemi Covid-19 sebagai Bencana Non Alam Medis dalam Menetapkan Force Majeure di Indonesia - Peni Jati Setyowati (Universitas Muhammadiyah Purwokerto, 2021)
A contract forms a private entity between the parties involved, herein each party has the legal rights to demand the implementation or fulfillment of all elements contained in the contract. However, such legal relationship through the contract does not always fulfil the expectation and purpose. This might occur because the involved parties have committed breach of contract / default. Such condition can occur and be done by both parties because of coercion, error, fraud, or force majeure. In a more specific context, there are several causes of force majeure. The current condition of global pandemic of covid-19, including in Indonesia, has affected the implementation of an ongoing contract between involved parties becomes disrupted, even can result in null or not fulfilled the goals in the contract. Therefore, it is important for contract parties to understand more deeply about force majeure in responding to the latest condition. This normative legal research is intended to find out how the impact of the covid-19 pandemic on the force majeure clause of the contracts in Indonesia.Keywords: national disaster, covid-19, Indonesia, force majeure